Two sibs with microcephaly, hygroma colli, renal dysplasia, and cutaneous syndactyly: a new lethal MCA syndrome?. Issue 6 (1st June 1999) - Janssen, H C J P; Schaap, C; Vandevijver, N; Moerman, P; de Die-Smulders, C E M; Fryns, J-P
Abstract : We report two sibs of Turkish descent with multiple congenital anomalies including severe microcephaly, hygroma colli, cystic renal dysplasia, and bilateral cutaneous syndactyly of toes IV-V. In addition, the second sib presented with bilateral fusion of the eyelids, a bicornuate uterus, and clitoromegaly. The parents are first cousins, which suggests autosomal recessive inheritance. In reviewing previously published reports, several cases were found with cerebral, renal, and digital anomalies as the main features. Several of the additional symptoms present in the second sib were suggestive of Fraser syndrome, but the severe microcephaly in both sibs is unusual. The differential diagnosis is discussed, including the possibility of an entirely new entity in the broad spectrum of syndromes with cerebral, renal, and digital anomalies.